Analytical chemistry. Electrochemical methods of analysis study aid - Korotkova chemist Professor of Tomsk Polytechnic University, Doctor of chemical science; Voronova chemist Assistant of Tomsk Polytechnic University, Candidate of chemical sciences; Dorozhko chemist Engineer of Tomsk Polytechnic University; Lipskikh chemist engineer of Tomsk Polytechnic University (Tomsk Polytechnic University Publishing House, 2021)
This Study Guide consists of 6 chapters devoted to the theory and practice of electrochemical methods of analysis. The Study Guide covers the most important electrochemical methods of analysis: potentiometry, electrogravimetry, conductometry, coulometry, voltammetry and amperometry. The fundamentals of the theory of methods are presented, the hardware design is described, examples of practical use are given. The areas of application, advantages, limitations and disadvantages of the methods are discussed. Methods for establishing the qualitative and quantitative composition of a substance by an analytical signal are presented. The Study Guide is intended for foreign students studied the Analytical Chemistry at Tomsk Polytechnic University in accordance with Master Degree Program.